2017
DOI: 10.1080/19648189.2017.1304285
|View full text |Cite
|
Sign up to set email alerts
|

Porous structure optimisation of flash-calcined metakaolin/fly ash geopolymer foam concrete

Abstract: This study reports the production and characterization of geopolymer foam concrete (GFC). This material is foreseen for use as a self-bearing insulation material. In order to identify an optimal paste composition, eight mixtures were made and are presented in a ternary diagram (dry extract of alkaline solution, flash-calcined metakaolin (MK) and fly ash (FA)). The characterization of these pastes (initial setting time (IST), shrinkage and compressive strength) indicated an optimal composition corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Geopolymers can be a viable alternative to concretes based on Portland cement mainly due to the reduced CO 2 emissions (compared to OPC) [79,80]. The authors of [81] presented the results confirming that the CO 2 -e emission of geopolymer concrete is 9% less than OPC, despite the fact that many scientists previously claimed that it was a greater reduction value.…”
Section: Forecast and Summarymentioning
confidence: 98%
“…Geopolymers can be a viable alternative to concretes based on Portland cement mainly due to the reduced CO 2 emissions (compared to OPC) [79,80]. The authors of [81] presented the results confirming that the CO 2 -e emission of geopolymer concrete is 9% less than OPC, despite the fact that many scientists previously claimed that it was a greater reduction value.…”
Section: Forecast and Summarymentioning
confidence: 98%
“…Equations: H 2 O 2 + OH − ⟶ HO 2 − + H 2 O, and HO 2 − + H 2 O 2 ⟶ H 2 O + O 2 + OH − , represent the reactions during the foam formation [45]. It has been suggested that if the amount of H 2 O 2 is too high, the pores were not well distributed because of the bubble’s buoyancy [46]. Indeed, the effect of random distribution of the pores was observed for G and GM foams.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the coalescence of macropores observed in the G and GM foams can cause a decrease in the flexural strength found in these samples. Third, the presence of small cracks in the G foam (but not in GC) exposed to the acidic agent, can further increase the susceptibility of the basic geopolymer foams G. Fourth, the strength of the geopolymer material depends on the matrix strength [46]. Uniform dispersion of cotton fibres in the slurry could result in an improvement of the consistency of the matrix as well as high wettability between the fibres and the paste during the geopolymerisation process.…”
Section: Resultsmentioning
confidence: 99%
“…The composition was expanded using H 2 O 2 in amounts of 1, 1.5, and 2 wt.% and densities from 225 to 506 kg/m 3 and thermal conductivities from 0.07 to 0.12 W/mK were obtained. These studies have also shown that the use of surfactants has a huge impact on the porous structure [8]. It is also possible to use rice husks as a foaming agent [9].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the optimal parameters of the geopolymer foams, the metakaolin and fly ash are often used together. Samson and Cyr [8] proved that the most optimal composition for their type of raw materials was 62.5% metakaolin with 12.5% fly ash and 25% activator. The composition was expanded using H 2 O 2 in amounts of 1, 1.5, and 2 wt.% and densities from 225 to 506 kg/m 3 and thermal conductivities from 0.07 to 0.12 W/mK were obtained.…”
Section: Introductionmentioning
confidence: 99%